137k views
5 votes
Show your work and solve: 3(x - 5) = 2(x + 5)

User Rdaniels
by
4.6k points

2 Answers

4 votes

Answer: x=25

Explanation:

3(x - 5) = 2(x + 5)

3x-15=2x+10

x-15=10

x=25

User Ishan Rastogi
by
5.3k points
4 votes

Answer:

x = 25

Explanation:

Given expression:


\sf 3(x - 5) = 2(x + 5)

distribute inside parenthesis


\sf 3x - 15 = 2x + 10

collect like terms


\sf 3x -2x = 10+15

simplify following


\sf x =25

To check answer:

substitute x = 25 in equation


\sf 3(25 - 5) = 2(25+5)

simplify


\sf 3(20) = 2(30)

evaluate


\sf 60=60

As the statement is true, the answer is correct.

User Basia
by
5.1k points